Household Drinking Water Quality Surveillance (KAMRT) for Public and Environmental Health Improvement - Herniwanti, Herniwanti; Dewi, Oktavia; Rany, Novita; Nashabila, Rafni; Mitra (International Journal of Health Literacy and Science, 2025)
Access to safe drinking water is a key target under SDG 6.1; yet household-level risks remain under-monitored in Indonesia. This study aimed to assess household drinking-water quality in the Rumbai Bukit PHC area as part of the implementation of STBM pillar 3 by the Household Drinking Water Quality Surveillance (KAMRT). A crosssectional surveillance (July–Sept 2024) tested 24 household water samples from wells, PDAM, and refill depots for physical (colour, turbidity, odour, TDS), chemical (pH, Fe, Mn), and microbiological (E. coli) parameters. Laboratory examination showed that 22 samples (91.7%) were positive for E. coli, with the highest contamination detected in dug-well (100%) and refill-depot water (87.5%), while only one PDAM sample was positive. In addition, three parameters, pH (33.3%), Fe (25%), and Mn (20.8%), failed to meet the national standards set in the Ministry of Health Regulation No. 2/2023. No samples failed for colour, odour, turbidity, or TDS. Most household water was unsafe microbiologically. Strengthened internal/external monitoring, public education on safe storage/treatment, and multisector collaboration using community-based technologies are required to secure sustainable safe water access.